Proximate composition of wild meats present in traditional food systems of the Brazilian Amazon - Thales Daniel Oliveira de Lima e Silva; Andrezza Cavalcante Nunes Matias; Elias Jacob de Menezes Neto; João Valsecchi do Amaral; Lorena Ianka Pontes da Silva; Michelle Cristine Medeiros Jacob; Juliana Kelly da Silva-Maia; Daniel Tregidgo (PLoS ONE, 2025)
The Amazon region, renowned for its rich biodiversity, is home to indigenous and riverside populations that maintain an intrinsic relationship with the forest, playing a crucial role in the local ecological balance. The diet of this population, based on fish and wild meat, is essential for their food security, providing proteins and other fundamental nutrients. However, the nutritional composition of these meats remains under-researched, limiting the development of appropriate nutritional strategies and interventions. This study aimed to characterize the proximate composition of mammal, bird, and reptile wild meat consumed within the context of a traditional food system in the Brazilian Amazon. A total of 78 samples were collected, including 51 mammals, 18 birds, and 9 reptile samples, from the Tefé National Forest, and the Amanã and Mamirauá Sustainable Development Reserves. The muscle tissues of the samples were analyzed following the official methods of the Association of Official Analytical Collaboration. Differences between taxonomic classes were evaluated using the Kruskal-Wallis test, followed by Dunn’s test with Bonferroni adjustment (P < 0.05) for those species with three or more replicates. Across all samples, descriptive statistics showed that the mean protein contents were 22.27 (1,32), 23.47 (1.7), and 22.31 (1.3) g/100 g of meat for mammals, birds, and reptiles, respectively. The mean ash contents were 1.08 (0.11), 1.27 (0.1), and 1.08 (0.13) g/100 g of meat, while the lipid contents were 5.72 (1,72), 5.40 (1.58), and 4.03 (0.53) g/100 g of meat for the same groups. Additionally, results indicated that macronutrient and ash (p = 0.13) levels did not differ significantly among classes: lipids (p = 0.07164) and proteins (p = 0.3055). When comparing the meats of wild mammals, birds, and reptiles with domestic meats typically consumed in modern food systems, a nutritional similarity was observed, highlighting their importance as key nutrient sources, particularly proteins. The data obtained provide a foundation for further research and will serve as a basis for strategies aimed at promoting food and nutritional security, contributing to the reduction of maternal and child malnutrition in Amazonian communities. Furthermore, the novel quantification of the proximate composition of wild meats underscores their role as a strategic resource for promoting health in these populations.